Habitat use of a critically‐endangered species in a predator‐free but degraded reserve in Australia. Issue 4 (1st December 2013) - Winnard, Amy L.; Stefano, Julian Di; Coulson, Graeme
Abstract : The success of species reintroduction programmes depends on many factors, including habitat quality and predator occurrence at release locations. For the critically endangered eastern barred bandicoot Perameles gunnii in Australia, successful releases have been achieved only in the absence of predation by the introduced red fox Vulpes vulpes . However, few fox‐free sites exist, but those that are fox free may have low habitat suitability, potentially leading to reintroduction failure. We studied a reintroduced population of eastern barred bandicoots at Mt Rothwell, a 420‐ha fox‐free reserve which appeared to have a degraded foraging range and a lack of nesting material due to overgrazing by marsupial herbivores. We quantified habitat use and measured several variables representing movement distances and nest use. Bandicoots foraged in open grassy areas and nested at sites containing high values of litter, lateral cover and concealment cover. Mean (± SE) home ranges (37.2 ha ± 11.8), daily movement distances (494.6 m ± 32.5) and distances between consecutive nests (122.6 m ± 29.0) were large for males. On average, the length of stay at each nest (2.8 days ± 0.4) was longer than previously recorded values for males, and 13.2% of the nests were used by at least two individuals, suggesting that nesting opportunities were limited. Despite behaviour indicating a low resource base, bandicoots appeared to be surviving and reproducing in our study area, indicating a capacity to live in structurally simple habitat in the absence of predators. Our results are consistent with predator exclusion being a critical factor for successful bandicoot reintroduction.